Efficacy and Outcome of Remdesivir and Tocilizumab Combination Against Dexamethasone for the Treatment of Severe COVID-19: A Randomized Controlled Trial - Mohiuddin Chowdhury, Abu Taiub Mohammed; Kamal, Aktar; Abbas, Kafil Uddin; Talukder, Shubhashis; Karim, Md Rezaul; Ali, Md. Ahsan; Nuruzzaman, Md.; Li, Yarui; He, Shuixiang (Frontiers in Pharmacology, 2022)
Objective: In this study, we investigated the efficacy and safety of remdesivir and tocilizumab combination therapy against dexamethasone for the management of severe COVID-19 patients. Methods: This was a multicenter study. Cases were randomly chosen and divided into two groups using an odd–even ratio of 1:1 applied to the hospital registration number. Group A received remdesivir [5 mg/kg (<40 kg) or 200 mg (>40 kg) on day 1 and then 2.5 mg/kg (<40 kg) or 100 mg (>40 kg) daily] + tocilizumab [8 mg/kg up to 800 mg highest 12 h apart], and group B was the control and received dexamethasone 6 mg/day. In addition, a broad-spectrum antibiotic and other essential treatments were received by all patients. To evaluate the mortality risk, the sequential organ failure assessment (SOFA) score was calculated on day-1. Treatment outcomes were measured as time to clinical improvement; mortality rate; duration of ICU stay; total period of hospitalization; the rate of (Supplementary Material) oxygen use; time to clinical failure; National Early Warning Score-2 (NEWS), and the percentage of lung recovery on CT of chest on discharge. Clinical trial registration ID: NCT04678739. Results: Remdesivir-Tocilizumab group had a lower mortality rate (25.49%) than the control (30.77%). The time to clinical improvement (Group A-9.41; B-14.21 days), NEWS-2 on discharge (Group A-0.89; B-1.2), duration of ICU stay (Group A-7.68; B-10.58), and duration of hospitalization (Group A-9.91; B-14.68) were less in the treatment group. Group A had a better percentage of lung recovery on chest CT than the control (Group A-22.13; B-11.74). All these differences were statistically significant (p= <0.05) in a t-test. However, no significant survival benefit was found among the study groups in Kaplan–Meier survival analysis, p = 0.739. Conclusion: The remdesivir–tocilizumab combination had preferable outcomes compared to the dexamethasone therapy for the treatment of severe COVID-19 concerning mortality rate and clinical and pulmonary improvement, although it did not demonstrate a significant survival benefit. Clinical Trial Registration:https://clinicaltrials.gov, NCT04678739.